Marginal literature paradigm in Iraq (Journal of the College of Basic Education, 2022)
This research attempts to study the phenomenon of marginal literature in Iraq, starting with the concept and the historical roots of the phenomenon, and ending with the model that we consider complete or ideal to embody the accurate description of marginalization. In it, the phenomenon in Iraq through many well-known models in cultural life, then we chose for the third topic an integrated model that represents the phenomenon in life and poetry, after that we appended the three topics to a conclusion in which we showed the importance of marginal literature that embodies the variables of daily life at its various social, economic and political levels.